2020
DOI: 10.1200/jco.2020.38.4_suppl.66
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based detection of early-stage colorectal cancer using multiomics and machine learning.

Abstract: 66 Background: Despite population screening efforts, screening rates for colorectal cancer (CRC) remain suboptimal. A non-invasive, blood-based screening test with high sensitivity and specificity in early-stage disease should improve adherence and ultimately reduce mortality; however, tests based only on tumor-derived biomarkers have limited sensitivity. Here we used a multiomic, machine learning platform to discover, refine, and combine tumor- and immune-derived signals to develop a blood test for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The study showed that 5hmC profiles of cfDNA are a strong predictor of cancer, including high sensitivity for the detection of early-stage cancer. The performance achieved in this large well-controlled study with internal validation is at least comparable to performance in CRC reported for other analytes 8 , 12 , 32 34 and for 5hmC in smaller studies 13 , 14 . Our data suggest that the 5hmC signal derived from epigenetic changes in cfDNA is more sensitive at an early stage than that from other analytes.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…The study showed that 5hmC profiles of cfDNA are a strong predictor of cancer, including high sensitivity for the detection of early-stage cancer. The performance achieved in this large well-controlled study with internal validation is at least comparable to performance in CRC reported for other analytes 8 , 12 , 32 34 and for 5hmC in smaller studies 13 , 14 . Our data suggest that the 5hmC signal derived from epigenetic changes in cfDNA is more sensitive at an early stage than that from other analytes.…”
Section: Introductionsupporting
confidence: 76%
“…( C ) The 5hmC-based classifier performs comparably to reported classifiers for stage 1 CRC. To gain approximately comparable confidence intervals, 95% binomial confidence intervals were computed for all classifiers using publicly available information 8 , 12 , 33 , 34 , 38 . The CRC classifier from Putcha et al contains both Stage 1 and Stage 2 samples.…”
Section: Discussionmentioning
confidence: 99%
“…reported validation (not yet peer reviewed) of the classi er in a small validation set (n = 17) with a mix of stage 1 and 2 samples 33 . We include both the training and validation reports in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The group is optimistic on the future of MRD testing in CRC and anticipates that this type of testing will emerge as a standard component of clinical decision making as data continues to rapidly emerge. ctDNA based blood test (LUNAR-2) currently under investigation for use in detecting CRC in an average risk population ECLIPSE (NCT04136002): CRC screening study initiated in 2019; goal to enroll 10,000 patients ages 45 -84 planning to have a colonoscopy Grail 3,4 Pan-cancer early detection blood test utilizing cell-free (cf) nucleic acids (DNA and RNA) PATHFINDER (NCT04241796): prospective, multicenter study enrolling~6,200 participants; primary goal is to guide appropriate diagnostic workup for different cancer types Freenome 5,6 Multiomics platform utilizing cfDNA, cfRNA, proteomics, epigenetics, as well as computational biology and machine learning methods to generate early tumor and immune cancer signatures PREEMPT CRC (NCT04369053): clinical study enrolling~14,000 average risk participants undergoing colonoscopy; primary goal is to validate blood based test for CRC screening Exact Sciences 7,8,9 ColoGuard Table 5. Use of Molecular Assays in CRC: Summary of GICTEG Practice Points…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although not intended to be a comprehensive list of all CRC and/or pan-cancer screening tests that are currently under investigation, Table 1 provides an overview of some of the genomic tests and technologies that have been used to screen for CRC, including commercially available and investigational tests [1][2][3][4][5][6][7][8][9]. These noninvasive tests aim to assess for genomic and epigenomic changes in bodily fluids (i.e., "liquid biopsies"), which can detect the presence of cancer.…”
Section: Genomic Testing In Crc Screening and Ongoing Clinical Trialsmentioning
confidence: 99%